Pinto Beans (Phaseolus vulgaris L.) Lower Non-HDL Cholesterol in Hamsters Fed a Diet Rich in Saturated Fat and Act on Genes Involved in Cholesterol Homeostasis - Nguyễn, Tiến An (2023)
Pinto beans contain multiple active agents such as polyphenols, flavonoids, and saponins, and have been shown to lower cholesterol, but the mechanisms involved in this effect have not been explored.